Divorce and the birth control pill - Miriam Marcen (European Regional Science Association (ERSA), 2013)
This paper explores the role of the birth control pill on divorce. To identify its effect, we use a quasi experiment exploiting the differences in the language of the Comstock anti-obscenity statutes approved in the 1800s and early 1900s in the US. Results suggest that banning the sales of oral contraceptive methods has a negative impact on divorce. These findings are robust to alternative specifications and controls for observed (such as female labour force participation, or changes in the early legal access to the birth control pill) and unobserved state-specific factors, and time-varying factors at the state level. Additional analysis, developed to examine whether the impact of subsequent divorce law reforms on divorce is modified after controlling for the birth control pill effect, shows that, although sales bans matter, the impact of divorce law reforms on divorce rate does not vary.
Keywords: J12; J13; J18; K36; 330; Divorce rate; birth control pill; sales bans; unilateral divorce